Aspartame in conjunction with carbohydrate reduces insulin levels during endurance exercise - Siegler Jason; Howell Keith; Vince Rebecca; Bray James; Towlson Chris; Peart Daniel; Mellor Duane; Atkin Stephen (Taylor & Francis Group, 2012)
Abstract Background As most sport drinks contain some form of non-nutritive sweetener (e.g. aspartame), and with the variation in blood glucose regulation and insulin secretion reportedly associated with aspartame, a further understanding of the effects on insulin and blood glucose regulation during exercise is warranted. Therefore, the aim of this preliminary study was to profile the insulin and blood glucose responses in healthy individuals after aspartame and carbohydrate ingestion during rest and exercise. Findings Each participant completed four trials under the same conditions (45 min rest + 60 min self-paced intense exercise) differing only in their fluid intake: 1) carbohydrate (2% maltodextrin and 5% sucrose (C)); 2) 0.04% aspartame with 2% maltodextrin and 5% sucrose (CA)); 3) water (W); and 4) aspartame (0.04% aspartame with 2% maltodextrin (A)). Insulin levels dropped significantly for CA versus C alone (43%) between pre-exercise and 30 min, while W and A insulin levels did not differ between these time points. Conclusions Aspartame with carbohydrate significantly lowered insulin levels during exercise versus carbohydrate alone.